ANALISIS FAKTOR PENGHAMBAT PROSES BELAJA MENGAJAR GURU MATEMATIKA SMA SE-KABUPATEN PULAU MOROTAI (Analysis of Problem Factors in learning process of Mathematics teachers) - Zulkifli Taib (EDUKASI, 2017)
This study is aimed to answer the question in this research such as: (1) wha problems are faced by the teachers in learning mathematics at Senior High school of Morotai? (2) what kinds of effort by the teachers in learning process? (3) what is the solution for the problems in learning process ? data collecting   technique   in   this   research   is   anklet,   questioners,   interview,   observation,   and documentation. The subject of this research is the of Mathematics subject at Senior High school Morotai Island which is consisted of 8 teachers. There are several angket which is possible to have as problem in learning process include of teachers, learning process, facility and learning evaluation. Generally, the result of this resereach shows that all the factors who have the potential to influence unsuccessable in learning mathematics subject. Otherwise, the dominant part here is the students who have a very low motivation and interest to learn mathematics subject. In overcoming   that problem, all the teachers in Morotai Island do not yet carry out an real action to solve the problem as well wich is only SMAll meeting that carry out in learning process. Based on the result of the research above, it can be concluded that learning problem is a complex problem which must be paid attention. That is why, even the SMAll barrier can also influence the learning success as well. And the teacher at once has very big responsibility that must innovate students in learning process as well. Key word: Faktor penghambat, belajar-mengajar, matematika